(untitled) - Werner, Jon M.; Jon M. Werner; Randy L. DeSimone (Mason OH, 2006)
Master the basics of human resource development with HUMAN RESOURCE DEVELOPMENT! Providing you with a clear understanding of the concepts, processes, and practices that form the basis of success, this management text shows you how concepts and theory can be put into practice in a variety of organizations. Coverage includes strategic issues in HRD, employee behavior, implementing HRD programs, training, research and statistics, and team-based coverage
Keywords: Personnel management; Career development